Carbon Dioxide Electrochemical Reduction by Copper Nanoparticles/Ionic Liquid-Based Catalytic Inks - Ruiz-Leon, D; Ruiz-Leon, D (Frontiers Media SA, 2024)
The development of copper nanoparticle (CuNP)-based catalysts for the electrochemical reduction of carbon dioxide (ECO2-R) offers a promising approach to enhance its transformation into other industrially significant compounds. This study reports ECO2-R at −1.3 V vs RHE using CuNPs and catalytic inks composed of CuNPs and ionic liquids (ILs), observing significant differences in the selectivity of each catalyst. Specifically, CuNPs alone show a preference for producing ethylene and aqueous products, such as formic acid, ethanol, and formaldehyde. In contrast, the addition of ILs to the catalytic system redirects selectivity toward gaseous products, with methane being the main product. These findings highlight the potential to optimize catalyst composition to tailor the selectivity of CO2 conversion processes. ILs modify the catalytic environment and influence reaction pathways, enabling the selection of specific products. © © 2024 Gazzano, Mardones-Herrera, Sáez-Pizarro, Armijo, Martinez-Rojas, Ruiz-León, Honores and Isaacs.